Broadband solar energy absorber based on monolayer molybdenum disulfide using tungsten elliptical arrays. (June 2020) - Li, Jiakun; Chen, Xifang; Yi, Zao; Yang, Hua; Tang, Yongjian; Yi, Yong; Yao, Weitang; Wang, Junqiao; Yi, Yougen
Abstract: Solar energy as an inexhaustible source of clean energy has attracted more and more attention. As an important way to collect source of energy, solar absorber is widely reported and studied. However, how to efficiently absorb the solar energy in the solar radiation range is a long-term perplexing problem. In this work, we propose a new type of broadband solar energy absorber based on monolayer molybdenum disulfide (MoS2 ). Tungsten (W) elliptical arrays are introduced into the structure to enhance its absorption. By exciting local surface plasmon resonance (LSPR) between monolayer MoS2 and tungsten elliptical arrays, ultra-broadband solar energy absorber with high absorption rate is obtained. Theoretical calculation by a finite-difference time-domain method (FDTD) shows that absorption with a bandwidth of 1750 nm from about 280 nm to 2030 nm has been achieved. The peak values of resonance wavelength at 1275 nm and 1885 nm are both greater than 99%. Our absorber also has good polarization independence and incidence insensitivity, which provides a theoretical basis for its work in the actual solar environment and possibilities for its application in other solar devices. The inspiration for proposed absorber can also be applied to other transition-metal dichalcogenides (TMDCs). Graphical abstract: We propose a broadband solar energy absorber based on monolayer molybdenum disulfide (MoS2 ) using tungsten (W) elliptical arrays. We find that the solar energy absorption efficiency is high and the operating region is extremely wide due to the combination of monolayer MoS2 and W elliptical arrays. Image 1 Highlights: The absorption efficiency can be effectively improved by combining MoS2 and W elliptical arrays. Our absorber has good operating band, polarization independence and incidence insensitivity. The proposed nanostructure can be used for other TMDCs materials.